Pengaruh Mobilisasi Dini ROM Pasif terhadap Waktu Pulih Sadar pada Pasien Lansia Pasca General Anestesi di RSD Gunung Jati Kota Cirebon - Dani, Dwi Darmawan; Novitasari, Dwi; Dewi, Feti Kumala (Pustaka Galeri Mandiri, 2025)
As people age, physiological changes significantly impact the cardiovascular, respiratory, renal, and central nervous systems, as well as drug elimination processes. These changes make elderly individuals more vulnerable to the side effects of general anesthesia, potentially prolonging recovery time and increasing the risk of postoperative complications. This study aims to assess the effect of early passive Range of Motion (ROM) mobilization on the recovery time of consciousness in elderly patients post-general anesthesia at RSD Gunung Jati, Cirebon. The study used a quasi-experimental design with a posttest-only non-equivalent control group. A total of 42 elderly patients participated, divided into two groups: 21 patients in the intervention group who received 10 minutes of passive ROM mobilization, and 21 patients in the control group who received standard postoperative care. Recovery of consciousness was assessed using the Modified Aldrete Score, monitored every 5 minutes until a score of ?9 was achieved. Data were analyzed using the Shapiro-Wilk test for normality and the Mann-Whitney test to examine the effect of ROM mobilization on recovery time. The results showed the intervention group had a mean recovery time of 22.86 minutes (SD 2.28), compared to 27.14 minutes (SD 6.90) in the control group. Statistical analysis revealed a significant effect (p < 0.000). These findings support the claim that early passive ROM mobilization effectively accelerates recovery of consciousness in elderly patients after general anesthesia and should be considered as an adjunct strategy in the Post Anesthesia Care Unit (PACU).